THE STUDENT’S READING COMPREHENSION OF PROCEDURE TEXT AT XI GRADE OF OFFICE ADMINISTRATION PROGRAM OF SMK YPLP PGRI BANGKINANG - Lia Puspa Rini Alnur (Journal of English Language and Education, 2019)
The objective of the research is to describe the students’ reading comprehension of procedure text. This research was conducted at SMK YPLP PGRI Bangkinang academic year 2016 – 2017. The subjects of this research consisted of 20 students of the second grade of office administration programme. The method of this research is descriptive research. The researcher used two instruments in this research, those were test and questionnaire. The test is used to know the students’ reading comprehension of procedure text. Meanwhile, the questionnaire is used to get specific informations by the students’ response dealing with the students’ reading comprehension of procedure text. Based on the data analysis of the research showed that the average of the students’ achievement at the second grade of office administration programme of SMK YPLP PGRI Bangkinang in reading comprehension of procedure text is 91. Furthermore, the students’ reading comprehension of procedure text at the second grade of office administration programme of SMK YPLP PGRI Bangkinang showed that 19 or 94%% students could understand and comprehend the procedure text. Meanwhile, 1 or 6% students could not understand of procedure text. It is concluded that the students’ reading comprehension of procedure text is categorized into Excellent.